Evaluation of Topical Matricaria chamomilla L. Oil Extract Activity on Linear Incisional Wound Healing in Albino Rats - M Jarrahi; M Zahedi; AA Taherian; H Miladi; H Safakhah (Institue of Medicinal Plants, ACECR, 2009)
Background: There are some information about antimicrobial and anti-inflammatory effect of Matricaria chamomilla flower oil extract, but there isn't any information about its effect on linear incisional wound healing. Objective: In this investigation, the effect of Matricaria chamomilla flower oil extract on linear incisional wound healing was studied. Methods: Thirty male Wistar rats were subjected to a linear 3cm incision made over the skin of the back. The animals were randomly divided into 3 experimental groups, as Sham operated, Control (Olive oil) and treatment. Sham group did not receive any treatment. Control group received topical olive oil twice a day from beginning of experiments to complete wound closure. Treatment group were treated topically by M. chamomilla extract dissolved in olive oil at the same time. For computing the percentage of wound healing, the area of the wound measured at the beginning of experiments and the next 2, 5, 8, 11, 14, 17 and 20 days. The percentage of wound healing was calculated by Walker formula after measurement of the wound area. Results: Results showed that there were statistically significant difference between treatment and Control animals (p<0.05) in most of the days. Conclusion: We conclude that the topical administration of M. chamomilla extract has wound healing potential in linear incisional wound model in rats.